Raising competitiveness and long-term growth of the Slovenian economy - Sila, Urban (OECD Economics Department Working Papers, 2015)
The rapid growth after independence stopped in 2008 as the global crisis exposed important structural weaknesses. Large state involvement and rigid labour and product markets lowered productivity. Weak corporate governance and easy credit before the crisis led to high indebtedness and overinvestment. Slovenia was slow to deal with the underlying structural problems. Gradually, important reforms have been implemented which raised credibility of Slovenia in the financial markets and boosted confidence. But economic recovery has been sluggish, many people are unemployed and living standards still remain below the pre-crisis levels. Cost competitiveness and export market performance deteriorated, and there have been marked improvements only recently. Better corporate governance and management practices in the state owned sector and privatisations can attract FDI and raise efficiency. Low innovative activity could be boosted by more FDI, stronger framework for entrepreneurial activity and better start-up support. Relatively high minimum wage is potentially reducing employment opportunities of low-skilled workers. Limiting the minimum wage growth, and lowering the high tax wedge on labour income could boost employment. Efficiency should be raised in early and tertiary education to enhance skills. Despite generous public support, overall students' performance could be improved and there are marked differences between students from different socioeconomic backgrounds. This Working Paper relates to the 2015 OECD Economic Survey of Slovenia (www.oecd.org/eco/surveys/economic-survey-slovenia.htm)